2012
DOI: 10.1007/s00276-012-1022-z
|View full text |Cite
|
Sign up to set email alerts
|

New anatomical data on the growing C4 vertebra and its three ossification centers in human fetuses

Abstract: PurposeDetailed knowledge on the normative growth of the spine is of great relevance in the prenatal diagnosis of its abnormalities. The present study was conducted to compile age-specific reference data for vertebra C4 and its three ossification centers in human fetuses.Materials and methodsWith the use of CT (Biograph mCT), digital image analysis (Osirix 3.9) and statistical analysis (Wilcoxon signed-rank test, Kolmogorov–Smirnov test, Levene’s test, Student’s t test, one-way ANOVA, post hoc RIR Tukey test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 31 publications
4
32
1
3
Order By: Relevance
“…Vignolo et al [26] reported that ossification started earlier in female fetuses, thus male fetuses were more difficult to assess in this respect. The present paper and our previous findings [4, 5, 2224] have not confirmed any sex differences in ossification of the spine. Therefore, in the present study both numerical data and statistical analysis are presented aggregately without taking sex into account.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Vignolo et al [26] reported that ossification started earlier in female fetuses, thus male fetuses were more difficult to assess in this respect. The present paper and our previous findings [4, 5, 2224] have not confirmed any sex differences in ossification of the spine. Therefore, in the present study both numerical data and statistical analysis are presented aggregately without taking sex into account.…”
Section: Discussioncontrasting
confidence: 56%
“…Of note, such a proportionate increase in cross-sectional area was previously proved by Baumgart et al [5] for vertebra C4 as y  = −4.690 + 0.437 × age, and by Szpinda et al [23, 24] for both vertebrae T6: y  = −15.591 + 1.200 × age and L3: y  = −32.423 + 2.071 × age.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations